Narrow-band UVB phototherapy does not consistently improve quality of life in psoriasis patients: A prospective observational study from Eastern India - Shweta Arora; Bikash R Kar (Wolters Kluwer Medknow Publications, 2018)
Introduction: Psoriasis is a chronic inflammatory and proliferative condition of the skin which is well-known to impair the patients' quality of life (QoL). Of the various treatment modalities, narrowband UVB (NBUVB) phototherapy is one of the standard treatments for moderate to severe plaque psoriasis with minimal side-effects compared to other systemic therapies. Objectives: To study whether NBUVB phototherapy administration improves QoL in plaque-type psoriasis and to find the correlation between clinical severity of psoriasis and patients' QoL by using psoriasis area severity index (PASI), dermatology life quality index (DLQI), and psoriasis disability index (PDI) tools before and after NBUVB phototherapy. Materials and Methods: Thirty-seven patients with plaque psoriasis involving >10% of body surface area (BSA) underwent NBUVB phototherapy thrice weekly for 36 sessions. Clinical severity of psoriasis was assessed by PASI and impact of psoriasis on quality of life by DLQI and PDI. Assessment was done at the baseline, 18th, and 36th session. Results: After 36 sessions of NBUVB phototherapy, mean reduction in PASI was 79.6% which was statistically significant. On the other hand, DLQI and PDI did not show significant improvement and did not correlate with PASI. Conclusion: NBUVB phototherapy reduces clinical severity of psoriasis. However, clinical severity and QoL impairment is independent of one another. DLQI and PDI do not improve proportionate to clinical improvement.